Social Enterprises as Agents of Social Justice: A Rawlsian perspective on institutional capacity - Lechterman, Theodore; Mair, Johanna (SAGE Journals, 2024)
Many scholars of organizations see social enterprise as a promising approach to advancing social justice but neglect to scrutinize the normative foundations and limitations of this optimism. This article draws on Rawlsian political philosophy to investigate whether and how social enterprises can support social justice. We propose that this perspective assigns organizations a duty to foster institutional capacity, a concept we define and elaborate. We investigate how this duty might apply specifically to social enterprises, given their characteristic features. We theorize six different mechanisms through which social enterprises might successfully discharge this duty. These results affirm the value of conversation between organizational studies and political philosophy and shed new light on debates regarding social enterprise, institutional theory, and several other topics.
Keywords: Social enterprise; Social justice; Institutional capacity; Strong institutions; Political philosophy; John Rawls; 72 Filosofía; ODS 1 - Fin de la pobreza; ODS 5 - Igualdad de género; ODS 9 - Industria, innovación e infraestructura; ODS 10 - Reducción de las desigualdades; ODS 16 - Paz, justicia e instituciones sólidas